2013
DOI: 10.1370/afm.1511
|View full text |Cite
|
Sign up to set email alerts
|

Abbreviated Mindfulness Intervention for Job Satisfaction, Quality of Life, and Compassion in Primary Care Clinicians: A Pilot Study

Abstract: PURPOSE Burnout, attrition, and low work satisfaction of primary care physicians are growing concerns and can have a negative influence on health care. Interventions for clinicians that improve work-life balance are few and poorly understood. We undertook this study as a first step in investigating whether an abbreviated mindfulness intervention could increase job satisfaction, quality of life, and compassion among primary care clinicians.METHODS A total of 30 primary care clinicians participated in an abbrevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
395
3
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(436 citation statements)
references
References 24 publications
(35 reference statements)
15
395
3
14
Order By: Relevance
“…11,18,21 In contrast with other studies, there was no increase in empathy in the MBSR group. 17,18,20 One of the reasons for this may be because the student version of the JSE was used; this measured participants' opinions on empathic engagement in patient care rather than their own empathic behaviour.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 93%
See 1 more Smart Citation
“…11,18,21 In contrast with other studies, there was no increase in empathy in the MBSR group. 17,18,20 One of the reasons for this may be because the student version of the JSE was used; this measured participants' opinions on empathic engagement in patient care rather than their own empathic behaviour.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 93%
“…20 A more recent uncontrolled pilot study in primary care clinicians (N = 30) showed that an abbreviated mindfulness course was associated with reductions in stress and work-related burnout. 21 The aim of the current study was to examine the feasibility and potential effectiveness of…”
Section: Introductionmentioning
confidence: 99%
“…A szociodemográfi ai adatok elemzésekor a kor 5 kategó-riás változóját használtuk (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) A munkával való "elégedettség" mérésére a "Ha újra dönthetne, az orvosi pályát választaná-e?" (Igen/Nem) kérdést használtuk indikátorként.…”
Section: Mérőeszközökunclassified
“…Ilyenek a kognitív viselkedésterápiás módszerek, meditáció, relaxáció, biofeedback-tréning és a testmozgás növelése [33]. A kiégés csökkentésére tett kísérletek között a mindfulness meditáció elsajátításán alapuló programok jelentik a legújabb irányvonalat, amelyek biztató eredményei szerint a képzést követően, és a követés során is, egyértelműen látszik, hogy a kiégés mindhárom komponense (emocionális kimerülés, deperszonalizáció, teljesítménycsökkenés) szignifi kánsan csök-kent a részt vevő egészségügyi dolgozók körében [34,35]. A fenti tréningek és képzések bizonyítottan pozitív hatása inspirálta, hogy elsőként adaptáljunk Magyarországon pozitív pszichológiai módszereken alapuló kiégésmegelőző tréninget (www.kiegesmegelozes.hu), amely fontos eszköz lehet a hazai orvosok és egészség-ügyi dolgozók kiégésének csökkentésében.…”
Section: Megbeszélésunclassified
“…These behaviors practiced by medical residents are associated with decreased symptoms of burnout and/or improved life satisfaction. [Fortney et al 2013;Lebensohn et al 2013].…”
Section: Focus On Wellnessmentioning
confidence: 99%